Genome-wide genotyping elucidates the geographical diversification and dispersal of the polyploid and clonally propagated yam (Dioscorea alata L.) - Sharif, B.M.; Burgarella, C.; Cormier, F.; Mournet, P.; Causse, S.; Van, K.N.; Kaoh, J.; Rajaonah, M.T.; Lakshan, S.R.; Waki, J.; Bhattacharjee, Ranjana; Gueye, B.; et al. (Oxford University Press, 2020)
Background and Aims Inferring the diffusion history of many human-dispersed species is still not straightforward due to unresolved past human migrations. The centre of diversification and routes of migration of the autopolyploid and clonally propagated greater yam, Dioscorea alata, one of the oldest edible tubers, remain unclear. Here, we address yam demographic and dispersal history using a worldwide sample.